Celastrus orbiculatus extract inhibits the migration and invasion of human glioblastoma cells in vitro. Issue 1 (December 2016) - Gu, Hao; Feng, Jun; Wang, Haibo; Qian, Yayun; Yang, Lin; Chen, Jue; Jin, Feng; Shi, Youyang; Lu, Songhua; Liu, Yangqing
Abstract Background Gliomas are highly aggressive tumors of the nervous system, and current treatments fail to improve patient survival. To identify substances that can be used as treatments for gliomas, we examined the effect ofCelastrus orbiculatus extract (COE) on the invasion and migration of human glioblastoma U87 and U251 cells in vitro. Methods The effects of COE on cell viability and adhesion were tested using the 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide assay and cell adhesion assay, respectively. The effects of COE on cell migration and invasion were assessed by a wound-healing assay and transwell migration and invasion assays. The effects of COE on the expression of epithelial-mesenchymal transition (EMT)-related proteins and matrix metalloproteinases (MMPs) were evaluated using western blot and gelatin zymography, respectively. Finally, the effect of COE on actin assembly was observed using phalloidin-tetramethylrhodamine isothiocyanate labeling and confocal laser scanning microscopy. Results We found that COE inhibited the adhesion, migration, and invasion of U87 and U251 cells in a dose-dependent manner. COE reduced N-cadherin and vimentin expression, increased E-cadherin expression, and reduced MMP-2 and MMP-9 expression in U87 and U251 cells. Furthermore, COE inhibited actin assembly in U87 and U251 cells. Conclusions COE attenuates EMT, MMP expression, and actin assembly in human glioblastoma cells, thereby inhibiting their adhesion, migration, and invasion in vitro.